Improving basketball chest pass ability through push up exercises - Marsuna, Marsuna (Jurnal Patriot, 2025)
Problem: Chest pass ability in basketball requires optimal arm muscle strength. Many students show less than optimal chest pass technique due to weak arm muscle strength, so an effective training method is needed to improve it. Purpose: This study aims to determine the effect of push-up training on improving chest pass ability in basketball. Methods: This study used a randomized pre-test–post-test one group design with a sample of 30 male students aged 16–18 years. Push-up training was given for 6 weeks with a frequency of 3 times per week. Chest pass ability was measured using a ball throw-catch test against a wall as far as 3 meters for 30 seconds, before and after treatment. Data analysis used descriptive statistics and t-test. Result: The results showed a significant increase in chest pass ability after being given push-up training. The t-count value of 11.84 is greater than the t-table of 2.042, which means that there is a significant effect of push-up training on chest pass ability. Conclusion: Push-up training has been proven effective in improving basketball chest pass ability. This exercise can be used as one of the recommended arm muscle strength training methods in learning basic basketball techniques in schools.